Molecular Analysis of CYP2C19 Alleles and Clopidogrel Resistance Among Bangladeshi Patients with Acute Coronary Syndrome - Ahmed, Mohsin; Khan, Sayeedur Rahman; Razzaque, Aminur; Rahman, Mohammad Arifur; Islam, Shariful; Islam, Mainul; AKM, Monwarul Islam; Firoze, Mohammad Ullah; Rahman, Md Matiur; Ahmad, Tanveer; CM, Kudrat-E-Khuda; SA, Shiblee (Cardiology and Cardiovascular Medicine, 2023)
Background: Antiplatelet therapy is a cornerstone in the management of the Acute Coronary syndrome and the prevention of stent thrombosis after PCI. After aspirin clopidogrel is the widely used antiplatelet drug in our country. Many studies showed that clopidogrel resistance is the emerging problem for managing ACS patients and after coronary intervention. But exact data about clopidogrel resistance of Bangladeshi population is still unknown. Objectives: The purpose of the present study was to determine the prevalence of clopidogrel resistance among the Bangladeshi patients with Acute Coronary Syndrome. Methods: In this observational study a total 200 patients with Acute Coronary Syndrome were enrolled to see the prevalence of Clopidogrel resistance. Results: The mean age of the study population was 52.32±9.86 years and the study showed male predominance (84 % was male and 16 % was female). Female patients and smoker patients had higher incidence of clopidogrel resistance. Dominant CYP2C19 genotype was CYP2C19 (*1/*2) which was 52%. 33% of study population had CYP2C19 (*1/*1) genotype, 9% had CYP2C19 (*1/*17) genotype, 3 % had CYP2C19 (*2/*17) genotype, 2% had CYP2C19 (*17/*17) genotype and only 1% had CYP2C19 (*2/*2) genotype. In this study we found 44 % study population was clopidogrel sensitive (Ultrarapid metabolizer: 11%, Extensive metabolizer: 33%). 56% study population had clopidogrel resistance (Intermediate metabolizer: 55%, Poor metabolizer: 1%). Conclusion: 56% of our study population was clopidogrel resistance among them 55% was intermediate metabolizer and only 1% was poor metabolizer.